Ideoloogilisest sõjast ei pääsenud keegi. EKP võitlus „kodanliku”massimeediaga. [No one escaped the ideological warfare. On the struggle of the Soviet Union Communist Partywith the “bourgeois” mass media on the example of the Estonian SSR’s printed media] - Miil, Marek (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2012)
Since the end of the 1960s the Estonian Communist Party (ECP) was in a complicated and unique situation as the higher party authorities declared that the ideological struggle within the Cold War keeps intensifying. At the same time, the Estonian Soviet Socialist Republic (ESSR) governed by the ECP was in addition to “the radio voices” in the influence sphere of the “bourgeois television” – the Finnish TV. The ECP tried to counter the bourgeois “ideological diversions” with an attempt to implement technical measures like signal interference or the sale impediment for TV set sound converter devices which enabled to watch the Finnish TV. For various reasons these efforts failed. As with the “radio voices”, one of the main methods that were used in the ECP’s anti-Finnish TV propaganda was the “uncovering”, thus creating an image of the enemy. This image of the bourgeois television and the Western propaganda apparatus was meant to facilitate discrediting the trustworthiness of the Finnish TV as well as other “bourgeois” media channels in the eyes of the ESSR’s inhabitants and hold the citizens in the influence sphere of domestic mass media.(Longer version of the current abstract is included in the article, starting from p 280.)